MEDIA AND CUSTOMERS: (An analytical study of the opinions and attitudes of a sample of industrialists in the role of media in directing consumers to national industries) - Jasem , Raad; Turky, Muna; Fadel Al-Hakim, Hula (ALBAHITH ALALAMI, 2007)
The talk about the relationship between the media and industrialists can be the core of a bigger and deeper subject which is the role of these means in increasing sales : First, increasing the customer’s awareness of the importance of goods and the result of the promotion of products. Secondly, increasing investments which do require continuous studies and deep research in order to understand the constantly changing market conditions, and the public’s taste. In this research, we try to find out how industrialists see the role of media in the promotion of products in Iraq today, and how it develops in the future. There was a reluctance of the industrialists to advertise in the local media, also industrialists see the role of the local media in advertising products as ambiguous. Therefore, the following questions demand answers: 1- What media channels do industrialists prefer to promote their products ? 2- What are the reasons for the reluctance of local producers to advertise in the local media? 3- Does the local media provide appropriate facilities for industrialists ? The search aims to: 1- Disclose the industrialists’ opinions in the role of media in promoting local products. 2- Bring to light the reasons behind the reluctance of producers to advertise in the local media. 3- Determining the problems of the industrialists regarding their opinion of the role of the media in promoting local products and their vision for the development of the role of the media and their proposals in this regard. The research was divided into a methodological framework that includes the research problem and its procedures, and also into a theoretical framework that deals with the concept of economic media and its features. Then, the concept of advertising and its characteristics in the three types of media, the press, radio and television, and finally the global media’s interest in funding advertisements, while the applied framework was an analysis of the questionnaire forms prepared by the researchers to reach and discuss the results.